(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine a point score system for predicting the likelihood of blood transfusion after Shoulder and elbow arthroplasty. Methods: The current study represents a retrospective analysis of all shoulder and elbow arthroplasties performed at the Manor Teaching Hospital United Kingdom by the senior surgeon/Author from Jan 2010 to Dec 2014. A database of 183 patients that underwent elective surgery at a teaching hospital was used for analysis to determine potential variables that was predictive of blood transfusion. The predictor variables evaluated included type of arthroplasty (shoulder vs. elbow, primary vs. revision, trauma vs. arthritis.) and age, sex, and medical co morbidity. The outcome variable was allogeneic blood transfusion. Results: The record of 124 patients were reviewed. Females were 91(73.3%) and males 33(26.6%). The average age was 72 years (Range 39-91 years). There were 57(45%) primary arthroplasty surgeries involving the shoulder, 5 (4%) were shoulder revision surgery, 5 (4%) Delta shoulders for rotator cuff problems and one(0.7%) excision arthroplasty. Shoulder arthroplasty due to trauma was done in 30(24.1%) cases. There were 15 (12%) primary elbow replacements,11(8.7%) revision elbows and 4(3.2%) patients had elbow arthroplasty for trauma. One(0.8%) patient had Polaris hemi Arthroplasty for metastasis in shoulder and one(0.8%) patient had total elbow replacement for metastasis. Pre-operative Haemoglobin ranged from 9.4G/dl to 17.9G/dl (average 12.7) and post-operative Haemoglobin 6.8G/dl to 14.3G/dl (average 10.6). Blood transfusion (100 units) was done in 53(42%) patients. The average number of transfusion per patient was 1.88 (Range 1 – 4 units) with 28(65.1%) transfusions in arthroplasties for trauma,12(75%) transfusions in revision arthroplasties and 13(10%) patients with other procedures. The two most important variables which were highly significant were revision and trauma (p <0.001),while age was not very significant at all. Conclusion: It is possible to predict patients undergoing upper limb arthroplasty that will need postoperative blood transfusion Shoulder and elbow arthroplasty in trauma and revision cases are strong predictor of blood transfusion.